Enhancing Antiretroviral Therapy Adherence Among the Youth - Maina, Angela; Mwangi, Naomi (Academia Kenya, 2021)
Mbagathi District Hospital in Nairobi has approximately 300 youth (15- 24yrs) on ART. Viral load suppression for this group was 63 percent for the year 2016. Between 2016 and 2017, 40 percent of the youth initiated on care were lost to follow-up. The youth do not feel free to share their issues with clinicians and counsellors who are much older than them for fear of being condemned. Similarly, the counselling approach used is ‘old school’ and fails to attract the youth who would prefer interactive modern sessions that are more appealing to them (MacCarthy et al., 2018). The youth also lack peer mentors/counsellors and exposure to peer advocacy campaigns to encourage them in their journey towards viral suppression. Ignorance and poor attitude to ART also contribute to non-adherence as well as a lack of disclosure of their HIV status to their families and friends.
Keywords: Antiretroviral Therapy; Kenya